A man–vehicle e-passport system using biometric blockchain for automated border control - Xu, Bing; Bouridane, Ahmed; Ni, Qiang; Jiang, Richard (Frontiers in Blockchain, 2025)
Since the mid-1990s, the evolution of internet technologies has significantly transformed global connectivity and digital interaction. Today, advances in computing and networking continue to support the development of emerging paradigms such as the metaverse and digital twins—concepts that aspire to bridge physical and digital experiences. Parallel to this, blockchain technology is reshaping traditional notions of trust by enabling immutable transaction records and smart contract automation, thereby fostering the rise of decentralized autonomous organizations (DAOs). Building on these foundations, this study presents a biometric blockchain-based e-passport system designed to improve the operational efficiency of automated border control (ABC) systems. At the core of our approach is the concept of a DAO-inspired framework for border control wherein identity verification and management tasks are executed through atomic smart contracts and recorded immutably on the blockchain. Our system incorporates biometric authentication and decentralized identity features to digitize border documentation and automate verification processes. This creates a secure, verifiable digital representation of an individual’s identity that can interact with ABC workflows. Performance evaluations conducted using Hyperledger Caliper demonstrate the potential of the proposed system, showing a 3.5-fold improvement in processing efficiency compared to traditional ABC setups.